Perception of Pain With Bitewing, DIAGNOcam, and Teeth Separation Amongst Children - Osama M. Felemban; Jihan A. Khan; Najlaa M. Alamoudi; Eman A. El-Ashiry; Sara M. Bagher (Elsevier, 2024)
Background: This study evaluated the pain and discomfort associated with 3 diagnostic techniques for proximal carious lesions in children aged 5 to 8 years: bitewing (BW) radiographs, DIAGNOcam, and temporary teeth separation. Methods: The study included 60 healthy children between the ages of 5 and 8 years who had no prior history of dry mouth or mouth breathing, were definitely positive or positive based on Frankl Behavioral Rating Scale, had at least one pair of matched bilateral primary molars and/or permanent first molars in close contact with the adjacent tooth, and were free of restorations and frank cavitation. Each patient evaluated all 3 techniques. The pain and discomfort ratings were obtained by the Wong-Baker FACES Pain Rating Scale immediately after taking 2 standardised BW radiographs or undergoing use of DIAGNOcam and 2 days after temporary teeth separation with elastic separators by a single trained and experienced paediatric dentist. Results: The DIAGNOcam procedure resulted in much higher pain and discomfort (3.69 ± 3.10) than the other 2 diagnostic techniques. Within-participant pain and discomfort scored significantly higher with DIAGNOcam compared to BW radiographs (P < .001) and temporary teeth separation (P = .002). Conclusions: The DIAGNOcam diagnostic technique caused much more pain and discomfort than BW radiographs and temporary teeth separation using orthodontic elastic separators. The report is part of a randomised clinical trial that was registered at www.ClinicalTrials.gov under the identifier NCT03685058.